Another Brick in the Wall: Mohammad Nakhshab and the Foundations of the Left-Wing Interpretation of Islam in Contemporary Iran - Lolaki, Seyed Mohammad (Religious studies and theology, 2022)
Discussion concerning Islamic groups in Iran falls under three main schools of thought: leftist Islam, jurisprudential Islam, and liberal Islam. This article analyses the viewpoints of Mohammad Nakhshab, the founder of the modern left Islamic school and the Movement of God-Worshipping Socialists (Nehzat-e Khoda Parastan-e Sosialist) in contemporary Iran. This school has greatly influenced Iran in the modern era, starting with its role in the 1979 Islamic Revolution. The following paper focuses on the Pahlavi Dynasty, Nakhshab’s thought in relation to historical circumstances, his priorities for reform, his approach towards government and governance, and his understanding of public policy.